REWARD AND PUNISHMENT MANAGEMENT INOPTIMIZING THE LEARNING MOTIVATION OF MTSSTUDENTS. NURUL JADID RELIGIOUS LEADING PROGRAM - Rizal, Himmatur; Astutik Andayani, Sri; Abdullah, Abdullah; Saifuddin, Saifuddin; Zubaidi, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to determine: 1) To understand reward and punishment management in improving student learning 2) To optimize MTs student learning motivation. Nurul Jadid religious superior program, 3) To help achieve the curriculum in MTs. Nurul Jadid. This research uses descriptive qualitative analysis.